2022
DOI: 10.1097/j.jcrs.0000000000000837
|View full text |Cite
|
Sign up to set email alerts
|

Physician burnout in ophthalmology: U.S. survey

Abstract: Methods: A survey was distributed through email listservs to several national ophthalmology societies. Participants completed a modified Mini Z Burnout Survey, a 10-item questionnaire measured in 5-point Likert scales, followed by demographic questions. The Mini Z Burnout survey assessed 3 main outcomes: stress, burnout, and work satisfaction. The percentage of subgroups experiencing burnout were presented and comparisons made with odds ratios from logistic regression modeling. Results:Of the 592 ophthalmologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…Of 4077 retrieved studies, we reviewed 154 full-text articles, with 91 eligible studies published between 1995 and 2022 (Figure). Most studies (57 [62.6%]) were published in or after 2018 (eTable 1 in the Supplement).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of 4077 retrieved studies, we reviewed 154 full-text articles, with 91 eligible studies published between 1995 and 2022 (Figure). Most studies (57 [62.6%]) were published in or after 2018 (eTable 1 in the Supplement).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies (57 [62.6%]) were published in or after 2018 (eTable 1 in the Supplement). Eighty-seven studies were cross-sectional, and 4 studies were cohort. In the risk of bias assessment, 12 had low risk of bias (good), 68 were moderate (fair), and 11 were high (poor) (eTables 2 and 3 in the Supplement).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 This syndrome has been associated with higher rates of burnout, and indeed, a survey designed to quantify burnout among ophthalmologists in the U.S. and identify related risk factors showed that female ophthalmologists are nearly twice as likely to self-report burnout compared with men. 14…”
mentioning
confidence: 99%
“…12,13 This syndrome has been associated with higher rates of burnout, and indeed, a survey designed to quantify burnout among ophthalmologists in the U.S. and identify related risk factors showed that female ophthalmologists are nearly twice as likely to self-report burnout compared with men. 14 A discussion on the root causes of the mid-career dropout phenomenon related to women in medicine and on the other aforementioned gender disparities specifically in the area of cataract and refractive surgery is beyond the scope of this text because it would likely involve explicit and implicit bias and cultural factors, among others. It seems it will take many years for the incoming trainees to shift the balance as women climb the career ladder.…”
mentioning
confidence: 99%